Investigating the Intrinsic Motivation among Second Language Learners in Using Digital Learning Platforms during the Covid-19 Pandemic - Zuraina, Ali (AWEJ.org, 2022)
The study aims to investigate the intrinsic motivation among L2 in their uses of digital learning platforms during the Covid-19 pandemic. In particular, the central questions in the study are to identify the profiles of intrinsic motivation among L2 learners using digital learning platforms, determine gender differences using digital learning platforms, investigate the difference in motivation according to students' performances, and describe the perceived enjoyment of using digital learning platforms. The study that used a questionnaire to collect data among 72 engineering students found positive intrinsic motivation utilizing the medium to learn English. However, there was insufficient evidence to show a difference between gender using the digital learning platforms with intrinsic motivation. There was also insufficient evidence to prove that grades are associated with students' intrinsic motivation when the teacher assigned synchronous or asynchronous classroom tasks. Yet, the present study found that publishing works in Canva and writing posts on LinkedIn were among the students' most preferred digital learning platforms activities. The study is significant to teachers since it assists them in managing classes and discovering the uses of digital learning platforms for a conducive learning atmosphere during the pandemic. It is recommended that teachers need to be creative in using digital learning platforms to promote collaborative learning among learners.